H3K27 acetylation‐induced lncRNA EIF3J‐AS1 improved proliferation and impeded apoptosis of colorectal cancer through miR‐3163/YAP1 axis. Issue 2 (11th November 2019) - Liu, Dingsheng; Zhang, Hong; Cong, Jinchun; Cui, Mingming; Ma, Mingxing; Zhang, Fangyuan; Sun, Huayi; Chen, Chunsheng
Abstract: Long noncoding RNAs (lncRNAs) are found to be aberrantly expressed and pose significant impacts in colorectal cancer (CRC), the most prevalent type malignancy in the gastrointestinal tract. This study aimed to find out the regulation of lncRNA EIF3J antisense RNA 1 (EIF3J‐AS1) on CRC progression. Expressions of EIF3J‐AS1, microRNA‐3163 (miR‐3163), and Yes‐associated protein 1 (YAP1) in tissues and cells were evaluated by real‐time quantitative polymerase chain reaction (RT‐qPCR) and Western blot analysis. Association of EIF3J‐AS1 with CRC prognosis was analyzed through the online bioinformatics tool GEPIA. The biological function of EIF3J‐AS1 in CRC was investigated by Cell Counting Kit‐8, colony formation, caspase‐3 activity, and TUNEL staining. Competitive endogenous RNA (ceRNA) network of EIF3J‐AS1/miR‐3163/YAP1 was determined by luciferase reporter and RNA immunoprecipitation assays. Results showed that EIF3J‐AS1 was upregulated in CRC tissues and cell lines, indicating poor prognosis of CRC patients. The silence of EIF3J‐AS1 led to reduced proliferation and facilitated apoptosis of CRC cells. Mechanistcally, EIF3J‐AS1 was upregulated by cAMP‐response element‐binding protein‐binding protein‐mediated histone H3 on lysine 27 acetylation (H3K27ac) at the promoter region, and EIF3J‐AS1 upregulated YAP1 expression through sponging miR‐3163 in CRC cells. In conclusion, we first found that H3K27 acetylation‐induced lncRNA EIF3J‐AS1 improved proliferation and impeded apoptosis of colorectal cancer through the miR‐3163/YAP1 axis, which might potentially provide a novel molecular‐targeted strategy for CRC treatment. Abstract : EIF3J‐AS1 level was elevated in colorectal cancer (CRC), and silencing it reduced proliferation whilst increased apoptosis. EIF3J‐AS1 was induced by CBP‐mediated H327ac in CRC cells.